miR-468-3p suppresses osteogenic differentiation of BMSCs by targeting Runx2 and inhibits bone formation - Tao Fang; Ranxi Zhang; Feng Song; Xueru Chu; Qin Fu; Qianqian Wu (Journal of Orthopaedic Surgery and Research)
Abstract An improved understanding of the molecular actions underpinning bone marrow mesenchymal stem cell (BMSC) differentiation could highlight new therapeutics for osteoporosis (OP). Current evidence indicates that microRNAs (miRNAs) exert critical roles in many biological systems, including osteoblast differentiation. In this study, we examined miR-468-3p effects on osteogenic differentiation (OD). Distinct miR-468-3p reductions were identified during OD. MiR-468-3p also suppressed BMSC OD in gain- and loss-of-function assays, while it negatively regulated Runx2 as shown by molecular, protein, and bioinformatics approaches. When Runx2 was inhibited by small-interfering RNA (siRNA), the inhibitory effects of miR-468-3p toward BMSC osteogenesis were considerably reversed. Also, silenced miR-468-3p in ovariectomized (OVX) and sham mice augmented bone mass (BM) and bone formation (BF) and improved trabecular (Tb) microarchitecture. Therefore, miR-468-3p is a novel Runx2 regulator with key physiological action in BF and OD.